Errors in the evaluation of Arrhenius and van't Hoff plots. - Keleti, T (1983)
Errors in the numerical values of activation or normal enthalpies, entropies and free enthalpies calculated from Arrhenius or van't Hoff plots, respectively, are due to the neglect of equidimensionality in equations, or to inappropriate approximations. The logarithmization of dimensioned quantities should be avoided, which demands the use of relative concentrations if a change in mole number occurs in the reaction. The application of the Arrhenius plot to enzymic reactions by using Vmax./ET instead of the rate constant of product formation has meaning only if the reaction follows the simplest Michaelis-Menten mechanism; however, the use of the van't Hoff plot using Km is questionable even in the latter case.